Multiple paternity in a Pacific marine turtle population: maternal attributes, offspring outcomes and demographic inferences - Howe, M; FitzSimmons, N; Limpus, C; Clegg, S (Springer Berlin Heidelberg, 2017)
Variation in levels of multiple paternity (MP) among species, populations and individuals has important ecological and evolutionary ramifications including maintenance of genetic diversity and offspring fitness benefits. Within species, differences in breeding experience and body size may affect levels of MP via mate choice preferences. The present study tested these ideas in an Australian loggerhead turtle (Caretta caretta) population at Mon Repos Beach (24°48°S, 152°27°E, Queensland) to determine if variation in MP was related female breeding history or body size, or influenced embryo and hatchling outcomes in clutches from 29 females and 552 hatchlings. MP was moderately high (65.5%), but experienced females did not have higher levels of MP than first-time breeders (neophytes), nor was female size related to the number of sires. Instead, more subtle patterns emerged: multiply-sired clutches of experienced females were sired by more males than those of multiply-sired neophyte clutches and primary fathers sired a greater proportion of offspring when mated to larger females. These findings are consistent with cross-seasonal sperm storage in experienced breeders contributing to a small proportion of paternity and size-dependent variation in polyandrous mating behavior. MP did not influence offspring size, levels of within-clutch morphological variation or hatching success. However, the number of sires of a clutch was positively correlated with proportion of developed embryos, suggesting a fitness advantage of MP. From a population perspective, male-biased sex ratios likely contribute to the MP levels observed, and levels could decrease with projected feminisation of populations due to climate change.